2015
DOI: 10.1242/dev.119271
|View full text |Cite|
|
Sign up to set email alerts
|

Robust derivation of epicardium and its differentiated smooth muscle cell progeny from human pluripotent stem cells

Abstract: The epicardium has emerged as a multipotent cardiovascular progenitor source with therapeutic potential for coronary smooth muscle cell, cardiac fibroblast (CF) and cardiomyocyte regeneration, owing to its fundamental role in heart development and its potential ability to initiate myocardial repair in injured adult tissues. Here, we describe a chemically defined method for generating epicardium and epicardium-derived smooth muscle cells (EPI-SMCs) and CFs from human pluripotent stem cells (HPSCs) through an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 75 publications
3
142
3
Order By: Relevance
“…We also monitored key alternative cell fates (LPM and NCC) in the iPSC-derived PSM and SM states (), as these lineages are known to generate MSC-like cells under certain conditions. iPSC-derived LPM and NCC were acquired using previously published protocols (Iyer et al, 2015; Fukuta et al, 2014). The results showed that our induction methods preferentially lead iPSCs toward the paraxial mesoderm lineage, but not the LPM or NCC lineages.…”
Section: Discussionmentioning
confidence: 99%
“…We also monitored key alternative cell fates (LPM and NCC) in the iPSC-derived PSM and SM states (), as these lineages are known to generate MSC-like cells under certain conditions. iPSC-derived LPM and NCC were acquired using previously published protocols (Iyer et al, 2015; Fukuta et al, 2014). The results showed that our induction methods preferentially lead iPSCs toward the paraxial mesoderm lineage, but not the LPM or NCC lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Protocols have also been developed for the differentiation of EPDCs from human induced pluripotent stem (iPS) cells [46, 47]. However, since it is difficult to fully control the state of the iPS cell-derived EPDCs (fetal- or adult-like), they do not provide the opportunity to compare behavior of the developing and adult epicardium.…”
Section: Discussionmentioning
confidence: 99%
“…8284 Importantly, if BMP signalling persists for 3 days beyond when cardiac mesoderm is formed, cardiac progenitor cells differentiate into epicardial lineages instead of cardiomyocycytes. 85,86 The epicardium has been shown to serve as an important reservoir of cardiac fibroblasts and vascular smooth muscle progenitors in the developing heart, and plays an important role in cardiac repair after injury 87 . BMP signal transduction has been demonstrated in the atrioventricular canal, 88,89 and to a lesser extent in the cardiac crescent 8890 using BMP reporter mice, which harbour a BMP responsive element that regulates the reporter genes lacZ or GFP .…”
Section: H1 Bmps and The Cardiovascular Systemmentioning
confidence: 99%